AGIHAN ZAKAT IBN AL-SABIL DALAM REALITI SEMASA: Distribution of Zakah to The Ibn al-Sabil in The Current Reality - Abd Khafidz, Hasanah; Mohd Subri, Irwan (Jurnal Syariah, 2012)
This article discusses the status of the ibn sabil as one type of zakah recipient from the perspective of Islamic fiqh. It focuses on the application and the appropriateness of the distribution of zakah property to this type of recipient based on current needs and contemporary circumstances. The interpretations of scholars of legal texts from various sources are examined to verify the real status of the ibn sabil in the fiqh discourse. Four aspects related to the subject matter namely; individual status, sources, wealth and the objective are thoroughly discussed to determine the concept of the ibn sabil in the modern context and identify their eligibility to receive zakah property. The results of the study show that Islam has provided a â€œcontingency planâ€ to facilitate travellers in need of assistance in monetary form for inevitable obstacles. It also proves that the value of humanity is highly considered in the regulation and the implementation of zakah. The aspect of good governance in the practice of distribution, however, needs to be taken into serious consideration to avoid mismanagement.